Analisis Hukuman Disiplin Pada Peserta Didik - Khairi, Munadiyal; Sari, Rita (Diksi: Jurnal Pendidikan dan Literasi, 2022)
The purpose of the study was to find out how the application of time tokens in empowering students to learn from home in Civics lessons on the material of the State symbol / Garuda Pancasila. The method used in, this research is qualitative while data collection uses interview, observation and documentation techniques. The research subjects were 9 out of 21 students in grade 3 SDN Blang Awe. Where there are 3 students and 6 students who have difficulty in learning. Learning difficult hand over the coupon/talk card to researcher to make the process easier to t hand over the coupon/talk card to the researcher, to make the process easier learn how to teach. Through the time token model, it can help students reduce learning difficulties, both in terms of reading and speaking/expressing opinions